Effect of a public health protection scheme for the below-poverty-line population on out-of-pocket inpatient care expenditure in Bangladesh: findings from a quasi-experimental study - Md. Golam Rabbani; Md. Zahid Hasan; Gazi Golam Mehdi; Mohammad Wahid Ahmed; Md. Nurul Amin; Mohammad Shahadt Hossain Mahmud; Ziaul Islam; Shehrin Shaila Mahmood (BMC Health Services Research)
Abstract Background In Bangladesh, households’ out-of-pocket (OOP) health expenditure accounts for 68.5% of the total health expenditure. The Government of Bangladesh has been implementing a pilot health protection scheme called Shasthyo Surokhsha Karmasuchi (SSK) to protect the below-poverty-line population from higher financial burdens in accessing inpatient care since 2016. This study aimed to estimate and compare the OOP expenditures between patients enrolled in the SSK scheme and those not enrolled and identify the factors influencing OOP expenditures for inpatient care in Bangladesh. Methods We conducted a quasi-experimental study using an exit patient survey in 2021. A predefined standard method was used to identify the study population and among them, 314 randomly selected patients were interviewed. Simple statistics measures were employed for data presentation. The Kruskal-Wallis test and Wilcoxon Rank Sum test, and multiple log-linear regression models were applied to assess the effect of the SSK scheme and identify influencing factors. The regression results were then converted into exponentiated coefficients to facilitate interpretation of the effects on OOP health expenditures. Results The SSK patients incurred significantly lower OOP health expenditures, 3.15 times compared to non-SSK patients seeking inpatient care at SSK facilities, and 3.92 times compared to non-SSK patients at non-SSK facilities. After adjusting for covariates, SSK patients still had significantly reduced OOP health expenditures, 3.71 times lower compared to non-SSK patients at SSK facilities, and 4.36 times lower compared to non-SSK patients at non-SSK facilities. The difference in OOP payment for inpatient care across patient groups was led by direct medical OOP expenditure components. The medicine component was identified as the main driver of the OOP expenditure across patient groups. Residents of town and patients who stayed a single night at hospital experienced significantly reduced OOP expenditures for inpatient care. Among other variables, residents of towns and patients who stayed a single night at the health facility had significantly lower OOP expenditures for inpatient care. Conclusion The findings suggest that the SSK scheme reduces OOP expenses for beneficiaries and has a spill-over effect on non-beneficiaries. Ensuring service availability and accessibility is crucial for maximizing its benefits. Given its positive impact, scaling up SSK could further reduce OOP nationally and support the government’s health financing strategy (2012–2032).